2014 year in review: Cystic fibrosis. Issue 11 (7th September 2015) - Savant, Adrienne P.; McColley, Susanna A.
Summary In this article, we highlight cystic fibrosis (CF) research published in Pediatric Pulmonology during 2014, as well as related articles published in other journals. Pediatr Pulmonol. 2015; 50:1147–1156. © 2015 Wiley Periodicals, Inc.